Basic and Translational Applications of the Network Theory for Dystonia - Shaikh, Aasef; Sadnicka, Anna. (Cham : Springer International Publishing : Imprint: Springer, 2023)
A recently proposed novel scheme of dystonia suggests that it is a disorder of neural network. Impairment in any of the "nodes" of the network may result in deficient network activity, causing dystonia. This book aims to present various experimental evidence supporting the network theory of dystonia. Dystonia is the abnormal twisting and turning of the organ and associated involuntary oscillations. Although dystonia is less common than Parkinson's disease, traumatic brain injury, or stroke, each of these common disorders present with dystonia. Information regarding the brain regions that may be involved in dystonia is surprisingly limited and often conflicting. With chapters written by subject matter experts, this is a unique title that focuses on dystonia as a network disorder. This book would be of interest to basic and clinical researchers with an interest in motor systems and movement disorders.
Editorial -- Dystonia in childhood - how insights from paediatric research enrich the network theory of dystonia -- Focal Dystonia and the Stress-Network -- Limbic influences in Musicians dystonia -- Network perspective on task-specific dystonia -- Electromyography as a method for distinguising dystonia-like behavior in mice -- Deep brain stimulation of the interposed cerebellar nuclei in a mouse model of dystonia -- Applications of Transcranial Magnetic Stimulation for understanding and treating dystonia -- Brain connectivity in dystonia: evidence from Magnetoencephalography -- Dysfunctional networks in functional dystonia -- Collicular-pulvinar-amygdala axis and adult-onset idiopathic focal dystonia syndrome -- Neuromodulation in dystonia -- Electrophysiological properties of pallidal cells in cervical dystonia patients undergoing unilateral DBS -- Clinical implications of dystonia as a neural network disorder.
Keywords: Neurosciences; Neuroscience